Pengaruh Beban Pajak Tangguhan dan Cash Effective Tax Rate terhadap Persistensi Laba Pada Perusahaan Sektor Energi yang Terdaftar di BEI 2020 2025 - Fatiha Saadaturrohma; Yudiana Yudiana; Rasiman Rasiman; Ofan Maulana Yudista (Institut Nalanda, 2026)
This study aims to analyze the influence of deferred tax expense and cash effective tax rate (CETR) on earnings persistence among energy sector companies listed on the Indonesia Stock Exchange from 2020 to 2025. Adopting a quantitative approach, the sample was determined using purposive sampling, resulting in 16 companies and 96 observations. Data analysis utilized panel data regression, with the Fixed Effect Model (FEM) identified as the most suitable estimator. Partial results indicate that deferred tax expense has no significant effect on earnings persistence (p-value = 0.6113), suggesting that accrual tax fluctuations in the energy sector are viewed as routine technicalities. Conversely, CETR significantly impacts earnings persistence (p-value = 0.0000), demonstrating that cash tax management efficiency serves as a positive signal for earnings quality. Simultaneously, both variables significantly influence earnings persistence, with an Adjusted R-squared of 77.73%. This confirms that tax policies, particularly the cash dimension, play a dominant role in determining the sustainability of financial performance in energy firms. The findings provide empirical evidence that effective tax management can contribute to more stable and sustainable earnings, thereby enhancing investor confidence and supporting long-term corporate value creation in the energy industry.